Vascular responses of the rat to bradykinin - Lloyd, Sybil (1962)
The effects of oestrogens and of sympathetic blockade on the vascular response of rats to bradykinin were studied. No difference in response was found between males and oestrous or dioestrous females. The previous administration of an oestrogen did not affect the response. An augmentation of the depressor response to bradykinin was seen in both sexes after the intravenous administration of either dihydroergotamine or hexamethonium, but not after atropine. Pithing reduced the response to bradykinin. The differences between these results and those previously obtained with oxytocin are discussed.